(untitled) (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the role of peer group support on the psychology of adolescents with acne vulgaris. The method used is a descriptive analysis of literature studies obtained from various national and international journal references from 2020-2021. The results showed that peer support could provide positive energy, especially for adolescents with acne vulgaris prone to feeling insecure. In conclusion, psychological peer group support can increase self-confidence, reduce anxiety levels and prevent adolescents from committing suicide due to their Acne vulgaris infection. Keywords: Acne Vulgaris, Peer Group Support, Adolescent Psychology